2018
DOI: 10.3389/fmicb.2018.03079
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Synthesis and Transformation of Inorganic and Organic Chlorine Compounds

Abstract: Organic and inorganic chlorine compounds are formed by a broad range of natural geochemical, photochemical and biological processes. In addition, chlorine compounds are produced in large quantities for industrial, agricultural and pharmaceutical purposes, which has led to widespread environmental pollution. Abiotic transformations and microbial metabolism of inorganic and organic chlorine compounds combined with human activities constitute the chlorine cycle on Earth. Naturally occurring organochlorines compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 260 publications
0
54
0
Order By: Relevance
“…The chlorination of soil organic matter is primarily believed to be driven by biotic processes, but also include abiotic processes (Atashgahi et al 2018a(Atashgahi et al , 2018b). The capability of chlorination among various groups of organisms are widespread including bacteria, fungi, and vascular plants is widespread (Clutterbuck et al 1940;Hunter et al 1987;de Jong and Field 1997;Öberg 2002;Bengtson et al 2009;Bengtson et al 2013).…”
Section: Org Levels In Plant Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…The chlorination of soil organic matter is primarily believed to be driven by biotic processes, but also include abiotic processes (Atashgahi et al 2018a(Atashgahi et al , 2018b). The capability of chlorination among various groups of organisms are widespread including bacteria, fungi, and vascular plants is widespread (Clutterbuck et al 1940;Hunter et al 1987;de Jong and Field 1997;Öberg 2002;Bengtson et al 2009;Bengtson et al 2013).…”
Section: Org Levels In Plant Biomassmentioning
confidence: 99%
“…Substantial chlorination of organic matter occurs in all types of soils from agricultural soils to forest soils (Gustavsson et al 2012;Redon et al 2013), and large spatial variability has been observed (Johansson et al 2003a, b). A large diversity or organisms harbour enzymatic capacity for chlorination and several hypotheses regarding the reasons for and regulation of the extensive natural chlorination have been proposed, but their verification is not yet conclusive (Bengtson et al 2009;Bengtson et al 2013;Atashgahi et al 2018a). Montelius et al (2015) observed extensive accumulation of Cl org in upper soil layers over 30 years in coniferous forests, while the accumulation was lower in deciduous forests.…”
Section: Introductionmentioning
confidence: 99%
“…The chlorine cycle consists of the biological, geological, and chemical processes that interconvert organic and inorganic chlorine compounds (Atashgahi et al 2018). Chlorine oxyanions are a group of inorganic chlorine compounds of particular interest in biology due to their high reduction potentials (E 0’ > 0.7 V) (Liebensteiner et al 2016, McCullough and Hazen 2003, Winterbourn 2008, Youngblut et al 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many pharmaceutical and agrochemical compounds as well as polymers are halogenated (Bolton et al, 2011;Lu et al, 2012;Jeschke, 2013), such as the commercially important antibiotics chloramphenicol, vancomycin and teicoplanin (Van Pée & Zehner, 2003). In nature, halogens including chloride, bromide, fluoride or iodide get attached to organic molecular scaffolds by halogenase enzymes, which have been detected in fungi, bacteria and algae from terrestrial and marine environments (Atashgahi et al, 2018;Latham et al, 2018). While marine enzymes preferentially halogenate with bromide (Neubauer et al, 2018), chlorinated compounds are regularly detected in terrestrial sources (Latham et al, 2018).…”
Section: Bioactive Compounds and The Role Of Halogenase Enzymesmentioning
confidence: 99%